Analisis Yuridis Putusan No.126/Pdt.G/2021/PN.Pbr Tentang Perbuatan Melawan Hukum - Rizki, Rizki; Anjelina, Indah (Universitas Medan Area, 2025)
This study will discuss the factors that cause the emergence of unlawful acts under Indonesia’s positive law and the judge’s considerations in Decision No. 126/PDT.G/2021/PN.Pbr concerning an unlawful act. The research employs a normative juridical method, which examines secondary legal materials such as books, legislation, online sources, interviews, and other relevant references. This study is qualitative in nature and refers to legal norms found in legislation, court decisions, as well as social norms developing within the community. The findings indicate that external factors are among the triggers of unlawful acts, namely elements or conditions beyond the direct control of the parties involved that influence the dispute in the case. The judge’s consideration in Decision No. 126/PDT.G/2021/PN.Pbr was that the Plaintiff’s claim could not prove the elements of an unlawful act as stipulated in Article 1365 of the Indonesian Civil Code (KUHPerdata), taking into account that the Defendant was able to present proof of payment through a third party. Therefore, the Plaintiff’s claim was deemed inadmissible and subsequently rejected.